2018
DOI: 10.1038/s41586-018-0140-0
|View full text |Cite
|
Sign up to set email alerts
|

Body-size shifts in aquatic and terrestrial urban communities

Abstract: Body size is intrinsically linked to metabolic rate and life-history traits, and is a crucial determinant of food webs and community dynamics. The increased temperatures associated with the urban-heat-island effect result in increased metabolic costs and are expected to drive shifts to smaller body sizes . Urban environments are, however, also characterized by substantial habitat fragmentation , which favours mobile species. Here, using a replicated, spatially nested sampling design across ten animal taxonomic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

35
240
5
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 228 publications
(281 citation statements)
references
References 44 publications
35
240
5
1
Order By: Relevance
“…The pattern of dominance of mobile species with increasing urbanization is a result fully in line with recent findings on body‐size shifts due to urbanization (Merckx, Souffreau, et al, ). This multi‐taxa study showed that butterfly and macro‐moth communities become increasingly dominated by larger species with urbanization.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The pattern of dominance of mobile species with increasing urbanization is a result fully in line with recent findings on body‐size shifts due to urbanization (Merckx, Souffreau, et al, ). This multi‐taxa study showed that butterfly and macro‐moth communities become increasingly dominated by larger species with urbanization.…”
Section: Discussionsupporting
confidence: 89%
“…The body‐size shift was interpreted as a shift towards increased mobility since body size is positively linked to mobility in Lepidoptera (Nieminen et al, ; Sekar, ; Slade et al, ; Stevens, Trochet, Van Dyck, Clobert, & Baguette, ). Rather than by the UHI‐effect, which would have caused shifts towards smaller body size for metabolic reasons (Merckx, Souffreau, et al, ), the body size of the urban communities of butterflies and moths appeared instead to be shaped mainly by the high degree of habitat fragmentation. It is obvious that the typically severe fragmentation of ecological resources in urban settings constitutes an effective filter on mobility, so that mainly the more mobile species are retained within urban communities (Sattler et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We found shrinking body size with elevated temperature along time series from the mixing to stratification periods. The smaller zooplankton taxonomic groups found in the stratification period were in line with recent investigations that warming benefits smaller organisms (Chiba et al, ; Merckx et al, ; Yvon‐Durocher et al, ). We also found that taxonomic groups differed in their body size response to temperature, which might be due to different food adaptability and competitive ability (Hart & Bychek, ; Sheridan & Bickford, ).…”
Section: Discussionsupporting
confidence: 89%
“…Knapp et al, ) and overall suggest that local climatic conditions, and resource availability and distribution are the main drivers of the assembly of urban communities from the regional pool. For instance in a meta‐analysis, Merckx et al () find body size changes among several taxa, possibly driven by both the urban‐heat‐island effect and habitat fragmentation. Similarly, our model city may select for cavity‐nesting bees because of the increasing availability of artificial cavities but also the corresponding lack of bare ground for ground nesting bees.…”
Section: Discussionmentioning
confidence: 99%